EVALUASI KINERJA TIM PENGELOLA APLIKASI SIKS-NG PADA DINAS SOSIAL KABUPATEN YALIMO - Albertus Bara'padang; Herman H; Muh. Irvan Nur’ Iva; Rahayu Rahayu (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2026)
This study examines the performance of the Social Welfare Information System–Next Generation (SIKS-NG) Management Team as the basis for the National Integrated Socio-Economic Data (DTSEN) at the Social Affairs Office of Yalimo Regency, Papua Pegunungan Province. Unlike previous studies that focused on technical aspects or accessible areas in Java and Sulawesi, this research fills a gap in the literature by analyzing operator performance in remote areas with geographical conditions. This study is among the first to explicitly apply William N. Dunn’s policy evaluation framework: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness—to evaluate the implementation of SIKS-NG in underdeveloped, frontier, and outermost (3T) regions. This research was conducted in accordance with Presidential Instruction Number 04 of 2025 concerning DTSEN, Minister of Social Affairs Regulation Number 03 of 2025, and Ministry of National Development Planning Regulation Number 07 of 2025. A qualitative descriptive approach was employed using in-depth interviews, participant observation, and documentation. Informants were selected through purposive sampling and included the Head of the Social Affairs Office, the Head of the Community Participation Division, SIKS-NG operators, staff, and social assistance beneficiaries. Data were analyzed using the Miles and Huberman model. The findings show that the implementation of the SIKS-NG application has been carried out but remains suboptimal. The main obstacles include delays in data updating, operator capacity, and inadequate internet infrastructure. Nevertheless, the management team continues to demonstrate commitment in delivering public services. Continuous training, infrastructure provision, and leadership support are identified as effective strategies for improving performance. Keywords: Operator Performance, SIKS-NG, DTSEN, Dunn’s Policy Evaluation Framework, Remote Areas, Public Administration